The two souls of Schopenhauerism: analysis of new historiographical categories - Miglietta, Giulia (Voluntas: Revista Internacional de Filosofia, 2021)
The Wirkungsgeschichte of Schopenhauerism is a complex mixture of events, encounters, influences and transformations. In order to orient oneself concerning such an articulated phenomenon, it is necessary to have valid hermeneutical tools at hand. In this contribution, I am going to propose a reading of the history of the effects of Schopenhauerism through new and effective historiographical categories that resulted from the research conducted by the Interdepartmental Research Centre on Arthur Schopenhauer and his School at the University of Salento. On the one hand, I will refer to Domenico Fazio’s studies on the Schopenhauer-Schuleand, on the other, to Fabio Ciracì’s research on the reception of Schopenhauer’s philosophy in Italy. This approach will reveal how the formulation of the so-called “two souls” of Schopenhauerism, the romantic and the illuministic, allows us to unravel the multifaceted panorama of the history of the effects of Schopenhauerian philosophy, in line with the subdivision within the Schopenhauer-Schule of metaphysical and heretical thinkers.